The Role of Trust Deficit on Business Sustainability in Freelance and Gig Economy Models - Aftuqa Sholikatur Rohmania; Eni Susanti (Universitas Sains dan Teknologi Komputer, 2024)
This study explores the role of trust deficit in the freelance and gig economy, where the business continuity of digital platforms heavily depends on worker trust and engagement. The research aims to examine how perceived lack of transparency, unclear procedures, and platform reliability affect worker loyalty and overall business sustainability. A mixed-methods approach with a sequential explanatory design was applied, combining quantitative data from 150 respondents collected through online and offline questionnaires and qualitative insights from 10 in-depth interviews with freelance workers and platform managers. The findings reveal that a higher trust deficit significantly reduces worker loyalty and participation, threatening platform stability, while transparent communication and clear procedural mechanisms mitigate these risks effectively. This research contributes theoretically by emphasizing trust deficit as a critical factor in sustaining digital labor platforms and offers practical implications for platform managers to enhance transparency, clarify operational procedures, and maintain long-term operational continuity in the gig economy